Communication technologies and their influence on language: Reshuffling tenses in Croatian SMS text messaging - Žic Fuchs, Milena (Array, 2008)
SMS text messaging has become one of the most dominant means of communication in Croatia. With respect to their linguistic features SMS text messages have become a lan-guage variety in their own right, exhibiting specific regularities in different aspects of language use. We investigate the use of tenses in Croatian SMS text messages in compa-rison to standard written Croatian. The results show a different distribution or reshuffling of past tenses, with a reappearance of tenses considered to be obsolete. We also look into the reasons that triggered off these changes as well as their impact on the Croatian tense system.